The Influence of Independent Curriculum Implementation and Teacher Competence on Improving the Quality of Basic Education: A Literature Review - Salsabila Dwi Fitri; Yorasakhi Ananta (Siber Nusantara Review, 2024)
This study aims to review the literature on the impact of the implementation of the Independent Curriculum and teacher competency on improving the quality of basic education in Indonesia. Through a literature review approach and systematic literature review (SLR), this article identifies the main dimensions that contribute to the success of the implementation of the Independent Curriculum and the development of teacher competency. The results of the study indicate that the Independent Curriculum, which emphasizes competency-based learning and student independence, has a positive correlation with the quality of basic education. In addition, teacher competency, including pedagogical mastery, professionalism, social, and personality, has been shown to play a crucial role in optimizing student learning outcomes. This article also builds hypotheses for future research.